2018
DOI: 10.1101/299412
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DeepSeqPan, a novel deep convolutional neural network model for pan-specific class I HLA-peptide binding affinity prediction

Abstract: Interactions between human leukocyte antigens (HLAs) and peptides play a critical role 1 in the human immune system. Accurate computational prediction of HLA-binding 2 peptides can be used for peptide drug discovery. Currently, the best prediction

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Multiple studies have been published for predicting the peptides binding the HLA-I alleles, which are compared with the proposed HLAB framework in this study, as shown in Figure 11 . These studies are Anthem [ 9 ], MixMHCpred2.0.2 [ 33 ], NetMHCpan4.1 [ 32 ], NetMHCcons1.1 [ 34 ], NetMHCstabpan1.0 [ 35 ], ACME [ 36 ], MHCSeqNet [ 37 ] and DeepSeqPan [ 38 ]. A fair comparison is carried out on the testing dataset using the HLAB models with the best performances on the validating datasets for the specific predicting tasks.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have been published for predicting the peptides binding the HLA-I alleles, which are compared with the proposed HLAB framework in this study, as shown in Figure 11 . These studies are Anthem [ 9 ], MixMHCpred2.0.2 [ 33 ], NetMHCpan4.1 [ 32 ], NetMHCcons1.1 [ 34 ], NetMHCstabpan1.0 [ 35 ], ACME [ 36 ], MHCSeqNet [ 37 ] and DeepSeqPan [ 38 ]. A fair comparison is carried out on the testing dataset using the HLAB models with the best performances on the validating datasets for the specific predicting tasks.…”
Section: Resultsmentioning
confidence: 99%
“…The first step toward developing a deep learning algorithm for PPI prediction is preprocessing the datasets to encode the categorical amino acids into a set of numerical values [95] . A common technique is one-hot encoding [95] , [96] , which may not be well-suited to problems with high cardinality, such as encoding proteins of significant length. For example, for a dataset comprising the twenty standard amino acids and an unknown amino acid (X), Alanine (A) might be represented as [10000000000000000000] using one-hot encoding, which is a simple vector with twenty zeros.…”
Section: Protein Representationmentioning
confidence: 99%
“…In the field of HLA binding, the HLA-CNN [35] , which uses three convolutional layers and two fully-connected layers with word embedding for encoding, achieves good performance and outperforms all traditional prediction methods. DeepSepPan [19] utilized the VGG-liked deep CNN to extract abstract features from HLA. Although it also achieves competitive performance compared with other current algorithms, DeepSeqPan loses flexibility and only supports the peptides which have 9 aa length.…”
Section: Feedforward Neural Network and Convolutional Neural Networkmentioning
confidence: 99%